A novel replication-independent histone H2a gene in mouse - Nishida, Hiromi (BioMed Central, 2005)
BACKGROUND: An uncharacterized histone H2a-coding transcript (E130307C13) has been cloned from a mouse full-length cDNA library. This transcript is encoded on chromosome 6, approximately 4 kb upstream of a histone H4 gene, Hist4h4. The proteins encoded by this transcript and the human H2afj mRNA isoform-2 have the highest amino acid similarity. In this paper, we characterize it from the expression pattern given by quantitative RT-PCR. RESULTS: Quantitative RT-PCR indicated that the gene that encodes E130307C13 (E130307C13) is regulated in a replication-independent manner, and therefore it is H2afj. Certainly, H2afj transcript lacks a stem-loop structure at the 3'-UTR but contains a poly (A) signal. In addition, its promoter region has a different structure from those of the replication-dependent histone H2a genes. CONCLUSION: The bioinformatics imply that E130307C13 is a replication-independent H2a gene. In addition, quantitative RT-PCR analysis shows that it is replication-independent. Thus, it is H2afj, a novel replication-independent H2a gene in mouse.